View in Botanical Gardens, Trinidad - (:unkn) unknown (Davidson and Todd, Ltd., Trinidad, 2009)
A view of a path in the Botanical Gardens passing through a variety of tropical trees and plants that make up the gardens.
Colour; Black and White; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens; Trees; Plants